Students’ Understanding on Cultural Concept: Case Study in Mathematics Department - Muhammad Arief Budiman (Bandar Lampung University (UBL), 2014)
The purpose of this research is to know how far the Mathematics students in 2013/2014 have ability to know the culture of the cultures in short stories. The method of this research is descriptive analysis. While the approach that we use is culture’s approach. Focus group discussion in this research is to find the result of analysis from the students. The result, first the students able to understand about the culture from the short stories that given. Second, almost the students do not know the short stories culture’s. Third, all of the students agree that Focus Group Discussion is a good technique to help the students understand the literary works.